ChemInform Abstract: Tellurites of Hexavalent Uranium: First Observation of Polymerized (UO4)2‐ Tetraoxido Cores. Issue 46 (27th October 2016) - Zadoya, Anastasiya I.; Siidra, Oleg I.; Bubnova, Rimma S.; Nazarchuk, Evgeny V.; Bocharov, Sergey N.
Abstract: Compounds (IV) and (VI) are characterized by powder and single crystal XRD.